IMPLEMENTASI TEKNOLOGI PEMBELAJARAN KAHOOT GEMBIRA SOLUSI PEMBELAJARAN JARAK JAUH - Lucia Prabawati Prasetyaningsih (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2021)
The prolonged pandemic period requires students to accept the fact that they cannot attend school for face-to-face learning as usual. The implementation of distance learning (PJJ), although on the one hand it is considered to have advantages, because it is able to provide solutions to the world of education during this pandemic, it has many weaknesses. The more time students participate in Distance Learning, the more it is felt that the feeling of boredom is increasingly felt by students. Learning also feels less effective. Facing this situation, SDN 01 Kulu Pekalongan Regency, is trying to find a new breakthrough as a solution in Distance Learning which is named "KAHOOT GEMBIRA". This assessment program is presented in the form of technology-based games which are very popular with children. The data collected shows that the enthusiasm of students to engage in learning, which was initially only 91 children or 69% involved, increased to 114 children or 86%, then decreased to 110 children or 83%. The original highest point was 9844, then decreased slightly to 9841, and finally increased back to 9843. The level of absorption of education units, which was originally 48%, increased to 52% and again increased to 56%. This innovative program, with game nuances but still containing elements of this learning, is proven to be able to overcome various problems faced in Distance Learning at SDN 01 Kulu, Pekalongan Regency.